ANALISIS INPUT-OUTPUT KOMODITAS KELAPA SAWIT DI INDONESIA - Hani Perwitasari; Pinjung Nawang Sari (MEDIAGRO, 2013)
Research is directed to determine backward linkage, forward linkage, the output, income, employment and gross value added multiplier effect of oil palm in Indonesia. Data used in the study are Input- Output tables Indonesia in 1975, 1980, 1985, 1990, 1995, 2000, 2003, 2005, and 2008 with 66 sector classification published by the Central Statistics Agency (BPS) by Input- Output analysis. Based on the survey results revealed that both backward and forward linkage of palm oil commodities is still below the average of all economic sectors in Indonesia . The multiplier effect of commodity output of palm oil is above the average of all sectors of the economy but the multiplier effect of income, employment and gross value added oil palm is still below the average of all economic sectors in Indonesia .Key words: input-output,  multiplier effect, palm oil, sectoral linkage.